Catalogue of ptyctimous mites (Acari, Oribatida) of the world - Niedbała, Wojciech; Liu, Dong (Zootaxa, 2018)
As important representatives of Oribatida (Acari), ptyctimous mites comprise more than 1400 described species in 40 genera and subgenera, with nearly cosmopolitan distribution except for the Arctic and Antarctic Regions. They are capable of folding the aspidosoma under the opisthosoma to protect their appendages, and are primarily soil and litter inhabitants, feeding on fungi and decaying plant remains with various levels of specificity. Our purpose was to provide a detailed catalogue of all known ptyctimous mite species in the world with information of distribution, taxonomic issues and some remarks. Data of known juvenile instars of ptyctimous mites which were not included in Norton & Ermilov (2014) were added. We hope that our catalogue with bibliography will be helpful in taxonomic and ecological studies. The catalogue presents taxonomic information and geographic distribution of 1431 known species of the world belonging to 42 genera and eight families (not including data of genus and species inquirenda, nomina nuda and species without author name). Among them, 261 species are listed as synonyms, 43 species inquirenda, nine homonyms, 17 new synonyms, one new subgenus Mahuntritia subgenus nov. and three new names are included in the catalogue.